2005
DOI: 10.1248/cpb.53.694
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Allyl Retrochalcone from the Roots of Glycyrrhiza inflata

Abstract: Two known retrochalcones, licochalcone A (1) and licochalcone C (2), and one new retrochalcone, licochalcone E (4) were isolated by cytotoxicity-guided fractionation from the roots of Glycyrrhiza inflata along with an ordinary chalcone, isoliquiritigenin (3). The structure of the new retrochalcone was elucidated through a spectroscopic analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
58
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 14 publications
1
58
0
1
Order By: Relevance
“…1) Although cell culture study has revealed concerning the cytotoxic effects of Lico-E on human tumor cells, 1) the molecular mechanisms of Lico-E for the cytotoxic effects were not addressed. In order to understand the apoptosis-inducing potential of Lico-E in cultured endothelial cells, human endothelial ECV 304 cells, which had undergone spontaneous immortalization from human umbilical vein endothelial cells, were used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1) Although cell culture study has revealed concerning the cytotoxic effects of Lico-E on human tumor cells, 1) the molecular mechanisms of Lico-E for the cytotoxic effects were not addressed. In order to understand the apoptosis-inducing potential of Lico-E in cultured endothelial cells, human endothelial ECV 304 cells, which had undergone spontaneous immortalization from human umbilical vein endothelial cells, were used.…”
Section: Discussionmentioning
confidence: 99%
“…We and other researchers identified the unusual phenolic compounds from Glycyrrhiza inflate, 1) known as retrochalcones, which are a form of normal chalcones that are structurally distinguished by the lack of oxygen functionalities at C-2Ј and C-6Ј (Fig. 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has a wide range of pharmacological, anti-bacterial and anti-oxidant activities (Varsha et al, 2013), hepato-protective (Chan et al, 2003;Jeong et al, 2002;Kimura et al, 2001), antiulcer (He et al, 2001), antiallergy (Park et al, 2004). anticancer (Fiore et al, 2004;Salvi et al, 2003;Yoon et al, 2005), antiviral activity against various DNA and RNA viruses (Fiore et al, 2008), including HIV (De Clercq, 2000) and severe acute respiratory syndrome-associated coronavirus (Cinatl et al, 2003). Biosynthesis of triterpenoids in licorice starts with conversion of two molecules farnesyl diphosphate (FDP) by the squalene synthase enzyme (SQS) to squalene (Lu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Although licochalcones A-D reportedly exhibit various biological activities, [5][6][7][8][9][10][11][12][13][14][15] the search for the biological activities of licochalcone E is only in the initial stage of intensive studies due to its recent discovery. Licochalcone E exhibits topoisomerase 1 inhibition 13 and induces endothelial cell apoptosis by modulating NF-kB and the Bcl-2 family.…”
mentioning
confidence: 99%